The mediational roles of harsh and responsive parenting in the longitudinal relations between socioeconomic status and Turkish children's emotional development. (November 2018) - Gülseven, Zehra; Kumru, Asiye; Carlo, Gustavo; Palermo, Francisco; Selçuk, Bilge; Sayıl, Melike
This study examined the associations among the socioeconomic status (SES) of Turkish families when children ( N = 340, Mean age = 83 months, SD = 3.59, 50.3% boys) were approximately 7 years of age (Time 1) and their emotional lability and emotion regulation tendencies 3 years later (Time 3). We also examined the mediating roles of mothers' harsh and responsive parenting behaviors when children were 9 years of age (Time 2). Results revealed that family SES was positively linked to parental responsiveness and negatively linked to harsh parenting; harsh parenting was positively linked to children's emotion lability and negatively linked to children's emotion regulation (after controlling for prior levels of emotion regulation and emotional lability at Time 2). Further, harsh parenting significantly mediated the associations between family SES and children's emotional lability and emotion regulation tendencies. The pattern of associations did not vary by child gender or community (e.g., Istanbul, Ankara, Bolu) in Turkey. The findings highlight the interplay among family SES, maternal parenting behaviors, and children's self-regulation outcomes in a non-Western, collectivist society.